An architecture for composition of services with heterogeneous interaction models - Huf, Alexis Armin (2018)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2018